The Safety of Tofu Food Produced in Klungkung Regency in Terms of Chemical and Microbiological Aspects - Sinta Purnamasari; A.A. Made Semariyani; I Nyoman Rudianta; I Putu Candra; I Wayan Sudiarta (SEAS (Sustainable Environment Agricultural Science), 2019)
This research was aimed at investigating the safety of tofu food in terms of chemical (formalin) and microbiological (E. coli and Salmonella sp.) aspects produced in KlungkungRegency that met SNI 01-3142-1998 requirements. The test was conducted in the Laboratory of the Great Hall of Denpasar Veterinary. This research was explorative research that used in-laboratory experiment design. The population of this research was obtained through the survey by conducting a survey, namely the number of tofu producers in KlungkungRegency that was 6 producers located in Klungkung Sub-District and Dawan Sub-District. The safety test of tofu food was conducted against formalin parameters (qualitative), E. coli and Salmonella sp. The result of this research from the six tofu samples showed negative content of formalin. Thus, the safety of tofu food based on the chemical (formalin) aspect had met the requirement by the Decree of the Health Minister of the Republic of Indonesia Number 722/Menkes/Per/IX/88 and the Decree of the Health Minister Number 1168/Menkes/Per/1999. The E. coli Microbe contamination which resulted